2018
DOI: 10.1177/1464884918809739
|View full text |Cite
|
Sign up to set email alerts
|

Filicide, journalism and the ‘disempowered man’ in three Australian cases 2010–2016

Abstract: How can journalism about parents killing their children improve public understanding of the factors influencing these filicide perpetrators? Three Australian cases occurring between 2010 and 2016 focus this question on stepfathers and foster fathers; a group recognised by international filicide research as of high risk for filicide. I consider questions of gender and masculine subjectivity in relation to Australian media coverage of filicide that involves these father figures so that a ‘disempowered man’, a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…While previous research tends to suggest that filicidal mothers and fathers are framed as bad, mad, or sad (Cavaglion, 2008(Cavaglion, , 2009Naylor, 2001;Saavedra & Oliveira, 2017) and comparisons of male and female offenders find female offenders portrayed as manipulative (Collins, 2016) or male offenders as more sympathetic (Elizabeth, 2016;Little, 2018), I find that mothers and fathers are portrayed positively, negatively, and sympathetically almost equally. Like prior research (Barlow, 2015;Collins, 2016;Greer & Jewkes, 2005), there is evidence of othering.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…While previous research tends to suggest that filicidal mothers and fathers are framed as bad, mad, or sad (Cavaglion, 2008(Cavaglion, , 2009Naylor, 2001;Saavedra & Oliveira, 2017) and comparisons of male and female offenders find female offenders portrayed as manipulative (Collins, 2016) or male offenders as more sympathetic (Elizabeth, 2016;Little, 2018), I find that mothers and fathers are portrayed positively, negatively, and sympathetically almost equally. Like prior research (Barlow, 2015;Collins, 2016;Greer & Jewkes, 2005), there is evidence of othering.…”
Section: Discussioncontrasting
confidence: 68%
“…This research may have only looked at the U.S. context, but these findings can translate cross-nationally. Prior research demonstrates commonalities of media portrayals of filicide across cultures with mothers framed as mad, bad, or sad in Australia (Naylor, 2001), Israel (Cavaglion, 2008), Portugal (Saavedra & Oliveira, 2017), and the U.S. (Huckerby, 2003), while fathers are framed more sympathetically portrayed in Australia (Little, 2018), Israel (Cavaglion, 2009), and New Zealand (Elizabeth, 2016). O' Brien and Culloty (2020) have already demonstrated that news coverage in Ireland is similarly offender-centric and minimizing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cavaglion (2009: 131) examined filicide by fathers in Israel and noted that the press ‘makes the story easy, clear, readable, understandable but also stereotyped’. Jewkes (2011: 147) and Little (2018) notes that sympathy is often shown towards men who kill their intimate partners in media reports that construe such events as a ‘tragic’ cases of decent husbands or doting dads gone wrong. While Fairburn and Dawson (2013) identified a reduction in the blame frame over time, from 29% in the 1970s to 14% in the late 1990s, they nonetheless found that coverage continues to employ victim-blaming news frames.…”
Section: Review Of Literaturementioning
confidence: 99%